2016
DOI: 10.1088/0957-4484/28/1/015101
|View full text |Cite
|
Sign up to set email alerts
|

Carbon nanotubes as carriers of Panax ginseng metabolites and enhancers of ginsenosides Rb1 and Rg1 anti-cancer activity

Abstract: A major benefit to nanomaterial based-medicine is the ability to provide nanosized vehicles for sporadic metabolites. Here, we describe how the conjugation of valuable ginseng secondary metabolites (ginsenoside Rb1 or Rg1) with carbon nanotubes (CNT) can enhance their anti-proliferative and anti-cancer effects. Ginsenoside-CNT conjugate (Rb-CNT or Rg-CNT) permitted the ginsenosides to be used at a low dose, yet achieve a higher incidence of cancer killing. We were able to demonstrate that the ginsenoside-CNT c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 57 publications
1
16
0
Order By: Relevance
“…In the present study, the Rg1 was administrated to CD34+CD38-LSCs, with the typical LSC phenotype [18,19,33]. The findings showed that Rg1 reduced the proliferation rate of CD34+CD38-LSCs, which was consistent with the findings from a previous study [34]. Also, the results of the evaluation of the cell cycle showed that Rg1 triggered G1 phase cell cycle arrest, which suggests that the effects of Rg1 on inhibition of cell proliferation of CD34+CD38-LSCs were induced by G1 phase arrest.…”
Section: Discussionsupporting
confidence: 90%
“…In the present study, the Rg1 was administrated to CD34+CD38-LSCs, with the typical LSC phenotype [18,19,33]. The findings showed that Rg1 reduced the proliferation rate of CD34+CD38-LSCs, which was consistent with the findings from a previous study [34]. Also, the results of the evaluation of the cell cycle showed that Rg1 triggered G1 phase cell cycle arrest, which suggests that the effects of Rg1 on inhibition of cell proliferation of CD34+CD38-LSCs were induced by G1 phase arrest.…”
Section: Discussionsupporting
confidence: 90%
“…The anticancer activities of Panax ginseng have been demonstrated by several studies (34,35). Ginsenosides, a group of bioactive compounds of Panax ginseng, exhibit anticancer activities (36,37). GRh2 has been demonstrated to inhibit cancer cell proliferation, migration and invasion, and prevent tumor growth and metastasis (24)(25)(26)(27)(28).…”
Section: Discussionmentioning
confidence: 99%
“…Specific characteristics such as purity and details of characterization of tubular CBNs were described in previous publications (Lahiani et al . , b). SWCNHs used in tests were synthesized and characterized in Center for Nanophase Materials Sciences, Oak Ridge National Laboratory as described by Lahiani et al .…”
Section: Resultsmentioning
confidence: 99%